Preliminary Evidence for a Window of Increased Vulnerability to Sustain a Concussion in Females: A Brief Report - La Fountaine, Michael F.; Hill-Lombardi, Vicci; Hohn, Asante N.; Leahy, Caroline L.; Testa, Anthony J. (Frontiers in Neurology, 2019)
A difference exists between sexes for the incidence of concussion injuries and severity of post-injury outcomes with females having a higher incidence rate (in comparable sports) and experience more robust symptoms than males. The basis for this disparity has remained largely unresolved. Recent findings point to a potential biological mechanism that may be related to the menstrual cycle as an arbiter of post-injury outcomes. What has not been addressed, is whether the phase of menstrual cycle (inferred fluctuations of ovarian hormones) contributes to an increased vulnerability to sustain a concussion injury. This prospective, observational study sought to determine if concussions occurred at different frequencies throughout the phase of the menstrual cycle. Female athletes who sustained a concussion injury were queried three times over the 7-day study (e.g., within 48 hours of injury, and 4 and 7 days after injury) to recall the number of days that have elapsed since the beginning of their most recent menstruation. Twenty female athletes enrolled after sustaining a concussion; 18 were eumenorrheic and 2 amenorrheic. Among eumenorrheic participants at the time of injury, 2 were in the follicular phase, 4 were in the early luteal phase and 9 were in the late luteal phase. Two athletes were injured on the first and 1 was injured on the second day of menstruation. The greatest number of concussions were sustained during the late luteal phase and during the first 2 days of menstruation. This 9-day window accounted for 2/3rd of the sustained concussions in our study